DUAL NATURE OF BUSINESS RISKS - Živanović, Cvijetin; Komarčević, Miodrag (ACADEMIC REVIEW, 2023)
In the paper, the authors problematize risk as a category that is involved in the daily life of individuals and/or companies, causing various problems on a personal and professional level. This should not be surprising because precisely at these levels of life and work, a person makes many different decisions every day based only on the assessment of the degree of probability that an event will or will not happen. In order to eliminate risks, people and companies and/or organizations can find themselves in different stages of dealing with risks: they control some risks directly, some indirectly, they seek support for some, etc. In the paper, the authors emphasize the importance of recognizing the nature of a possible event in order to determine the direction of the risk, bearing in mind that every risk is not negative and it may happen that an event that was initially characterized as high-risk ends successfully. The risk accepted in this way necessarily points to two specific categories: dualism and probablism. Both categories are significant for the simple reason that risks can never be completely eliminated but people must learn to control them.